Harnessing stimuli‐responsive biomaterials for advanced biomedical applications - Liao, Z; Liu, T; Yao, Z; Hu, T; Ji, X; Yao, B (Wiley Open Access, 2024)
Cell behavior is intricately intertwined with the in vivo microenvironment and endogenous pathways. The ability to guide cellular behavior toward specific goals can be achieved by external stimuli, notably electricity, light, ultrasound, and magnetism, simultaneously harnessed through biomaterial‐mediated responses. These external triggers become focal points within the body due to interactions with biomaterials, facilitating a range of cellular pathways: electrical signal transmission, biochemical cues, drug release, cell loading, and modulation of mechanical stress. Stimulus‐responsive biomaterials hold immense potential in biomedical research, establishing themselves as a pivotal focal point in interdisciplinary pursuits. This comprehensive review systematically elucidates prevalent physical stimuli and their corresponding biomaterial response mechanisms. Moreover, it delves deeply into the application of biomaterials within the domain of biomedicine. A balanced assessment of distinct physical stimulation techniques is provided, along with a discussion of their merits and limitations. The review aims to shed light on the future trajectory of physical stimulus‐responsive biomaterials in disease treatment and outline their application prospects and potential for future development. This review is poised to spark novel concepts for advancing intelligent, stimulus‐responsive biomaterials.